ДЭЛХИЙН УЛСУУДЫН ХӨГЖЛИЙН БОДЛОГО, ТӨЛӨВЛӨЛТ БА МОНГОЛ УЛС - С.МӨНХБАТ; Г.Цэнд-Аюуш (Politology, 2023)
In this era where globalization is pervasive in all areas and opportunities and risks for individuals, institutions, and nations increase, national Development Plan is the fundamental policy document that sets which country will realize in economic, social, and cultural areas in an integrated approach.Within the framework of the changing economic and social conditions in the world and in Mongolia, development plans have become a much more important instrument than they were in the past and due to these conditions, redesigning of those plans has become inevitable. In this article we would like to presented about development plan of Mongolia and other countries. Successive development plans adopted a scientific approach, making for the rational use of national resources, which enabled the Mongolia to achieve significant developments, exemplified by significant gains reflected in the various indicators of socioeconomic development. Accumulated development over the past decades has achieved significant improvement in standards of living and the quality of life.